Goacheeze Powder / Ainin Nadhirah Abd Manan ... [et al.] - Abd Manan, Ainin Nadhirah; Mohd Yusof, Mayamin Yusra; Roslan, Nor Syafini; Mohammad Zamri, Noor Nazzatul Syazana; Rashid, Siti Aishah (2021)
Cheese has grown in popularity in the worldwide in the last 50 years. Statistics show that consumption tripled from 1970 to 2009. Cheecah Sdn Bhd is introducing a new product to the customers which is Goacheeze as product invention made from goat milk cheese due to properties of cheese made from cow milk high in saturated fats and sodium content.Thus, it will results to the difficulty in digestion of the large fat molecule present. Besides, higher in lactose makes some people avoid from consumption because of the milk allergy or lactose intolerance. Due to the high sodium availability in the cow cheese, there are some of the consumer faced with severe conditions like hypertension and renal failure. Thus, we come out with a solution to produce dairy cheese product which provide high nutritious and can be consume for lactose intolerance consumer. Nutritionally, this product is relatively low in sodium content as two tablespoons of cow cheese cotains 511 mg of sodium, while same quantity of goat cheese only contains 118 mg of sodium. Besides, goat cheese contains smaller fat molecules making it easier to be digest as compared to the cow cheese. Low in lactose content of the goat cheese are suitable for the people with lactose intolerance, hence it is excellent choices for them.Goacheeze is a product invention made from goat milk cheese and turning into powder by using spray drying technology. Goacheeze powder are in stable dry form which can retain its shelf life in different storage conditions. Furthermore, Goacheeze powder also come in sachet which can be easier for travelling. Overall marketing strategy will be included specific marketing philosophy and strategy of the compant, the value chain and the channel of distribution which are by direct and online selling selling in the targeted market. Firstly, our target market will be focusing on the supermarket especially at urban area. As for our initial selling effort, we have already determined our target group of customers that would buy our products. Our main target customer is travellers as it is space saving and not perishable. Secondly, among cheese lovers due to multi ways of consumption include gourmet dipping, sauce and seasoning. Lastly, people with lactose intolerance because of the complication they faced when consume cow cheese. As our product comes in sachet, it will ease and minimise time to preapre as it does not require too much physical energy. This price of this product is also reasonable and affordable which is RM 33 for a box that contains 12 sachets of Goacheeze powder. The total net profit after all expenses are paid for second year is RM 79 000.00. The management team of our company are divided into several section which are Chairman, Non-Executive Director, Chief Executive Officer, Chief Financial Officer and Executive Director, Technical and Production. Each of the section were led by experienced and professional employee to ensure our company’s product quality and efficiency.